Zakah Management System Using Approach Classification - Zulfajri Basri Hasanuddin; Syafruddin Syarif; Darniati Darniati (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
The often problematic faced by Muslims are lack of understanding in calculating Zakah and determining the feasibility of compliant recipients based on Islamic Shari'a. This study aimed to establish Zakah management system to support calculation process based on Al Qaradhawi method, helping Board of Zakah in distributing Zakah funds to mustahik. The algorithm used for the classification of Zakah recipients is Naive Bayes. The classification was combination of discrete and continuous data which is conducted by experiments using feasible and unfeasible data as a novelty approach. The results have shown that the Naive Bayes method could solve the problem with 85% of average.